2007
DOI: 10.1002/mc.20263
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming of liver cells in tamoxifen‐induced rat hepatocarcinogenesis

Abstract: Tamoxifen, a nonsteroidal anti-estrogen, is a potent genotoxic hepatocarcinogen in rats, with both tumor initiating and promoting properties. Recently it has been demonstrated that genotoxic carcinogens, in addition to exerting genotoxic effects, often cause epigenetic alterations and these induced epigenetic changes may play important mechanistic role in carcinogenesis. In the present study, we investigated the role of tamoxifen-induced epigenetic changes in hepatocarcinogenic process. The results of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…It has been shown that genome-wide DNA hypomethylation in cancer, including liver cancer, largely affects repetitive DNA elements [28,40,41]. Additionally, recent evidence indicates that hypomethylation of retroelements occurs even in precancerous stages of development of human hepatocellular carcinoma [41,42], as well as at early stages of non-genotoxic and genotoxic rodent hepatocarcinogenesis [43,44]. Loss of cytosine methylation at repetitive DNA sequences is associated with increased transcription of these elements.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that genome-wide DNA hypomethylation in cancer, including liver cancer, largely affects repetitive DNA elements [28,40,41]. Additionally, recent evidence indicates that hypomethylation of retroelements occurs even in precancerous stages of development of human hepatocellular carcinoma [41,42], as well as at early stages of non-genotoxic and genotoxic rodent hepatocarcinogenesis [43,44]. Loss of cytosine methylation at repetitive DNA sequences is associated with increased transcription of these elements.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is the most stable epigenetic modification of mammalian genomes and is crucial for normal development, proliferation, and maintenance of genome stability [Jones and Gonzalgo, 1997;Rizwana and Hahn, 1999;Swales and Spears, 2005;Doerfler, 2006;Jones and Baylin, 2007]. DNA methylation patterns are disrupted in cancers [Jones and Gonzalgo, 1997;Feinberg and Tycko, 2004;Ehrlich, 2006;Jones and Baylin, 2007] and following exposure to genotoxic agents [Minamoto et al, 1999;Raiche et al, 2004;Tryndyak et al, 2007]. Differential methylation can arise in the germline; methylation changes at CpG sites in specific loci have been observed in the descendents of animals exposed to endocrine disrupting chemicals Skinner and Anway, 2005;Koturbash et al, 2006a] or ionizing radiation [Koturbash et al, 2006b].…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is the most stable epigenetic modification of mammalian genomes and is crucial for normal development, proliferation and maintenance of genome stability (29)(30)(31)(32)(33). DNA methylation patterns are disrupted in cancers (29,(33)(34)(35) and following exposure to genotoxic agents (36)(37)(38). Differential methylation has been observed in the descendents of animals exposed to various agents (39)(40)(41), suggesting a potential link to nontargeted DNA mutations and transgenerational effects.…”
mentioning
confidence: 99%